Inclusion and affective well-being: Roles of justice perceptions - Le, Huong; Jiang, Zhou; Fujimoto, Yuka *; Nielsen, Ingrid (Emerald, 2018)
Purpose – This paper examines the mediating roles of procedural justice and distributive justice in the organizational inclusion–affective wellbeing relationship. Design/methodology/approach – Data were collected from 253 Australian employees using an online survey. The study used confirmatory factor analysis and structural equation modeling to analyze the data. Findings – Organizational inclusion was positively related to both distributive justice and procedural justice. The relationship between organizational inclusion and affective wellbeing was mediated by both distributive justice and procedural justice. Research limitations/implications – The cross-sectional design may have limited the empirical inferences; however, the proposed model was based on robust theoretical contentions, thus mitigating the limitation of the design. Data were collected from a single organization, thus limiting generalizability. Practical implications – Implementation of inclusion training activities at organizational, group, and individual levels is important to enhance perceptions of organizational inclusion and subsequently improve employee affective wellbeing. Originality/value – Based on the group engagement model and group-value model of justice, this paper adds to the literature by demonstrating two mediating mechanisms driving the organizational inclusion–affective wellbeing relationship.